Neologisms as a Result of Partof- Speech Transformation and Transposition - SANTOYAN, AREN; PETROSYAN, LILIT (Bulletin of Yerevan University B: Philology, 2021)
In Linguistics, the term transformation is regarded as a part-of-speech transposition of the same meaning not only throughdifferent grammatical structures but also through different lexical means and ways. Neologisms are incessantly formed in the language. They are formed according to external special word building transfers – verb>noun, noun>verb, verb>adjective andsentence>word.Neologism compounds can be regarded as authorial transformation results of secondary clauses, word combinations and adverbial modifiers, descended from main clauses.
Keywords: linguistics, transformation, part-of-speech transformation, grammatical structure, neologism, neologism compounds